Quality of reporting inflammatory bowel disease randomised controlled trials: a systematic review - Anthony Akobeng; Svetlana Lakunina; Aditi Rane; Jamal Khudr (BMJ Open Gastroenterology, 2024)
Objective Our objective was to perform a systemic evaluation of the risk of bias in randomised controlled trial (RCT) reports published on inflammatory bowel disease (IBD).Design We assessed the risk of bias using the Cochrane tool, as indicators of poor methodology or subsequently poor reporting. We systematically selected, with dual independent judgements, all studies published on IBD with no time limits and assessed the methodological quality of included studies again using independent dual ratings.Results 563 full texts were included after selection and review. No abstract publications were free of any source of bias. Full-text publications still fared badly, as only 103 full-text papers exhibited a low risk of bias in all reporting domains when excluding blinding. RCTs published in journals with higher impact factor (IF) were associated with an overall reduced rate of being at high risk. However, only 6% of full RCT publications in journals with an IF greater than 10, published in the past 5 years, were free of bias.The trend over time is towards improved reporting in all areas. Trials published by larger author teams, in full-text form and by industry and public sponsorship were positively correlated with a lower risk of bias. Only allocation concealment showed a statistically significant improvement with time (p=0.037).Conclusion These findings are consistent with those of other specialties in the literature. While this unclear risk of bias may represent poor reporting of methods instead of poor methodological quality, it leaves readers and future secondary researchers with significant questions regarding such key issues.